The king is born - Rich, Richard; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Family Entertainment, 2005)
The story of the birth of Jesus, based on the Bible.
Includes Read-A-Long Sing-A-Long DVD entitled "The Birth of Jesus."
Includes Resource & Activity Book.
"Premium website accessible through DVD-ROM"--Container.
"NEST complete learning system."
DVD ; 2-channel Dolby surround sound.
In English with optional Spanish language track and optional English or Spanish subtitles ; scripture reference subtitles ; chapter access.
Keywords: Bible stories -- Juvenile films; Animated films; Children's films